Mabbollo Tradition in Bugis Marriage in Bone Regency Urf Perspective - Nuh, Ahmad; Saleh, Muhammad; Basri, St. Risnawati; Raziq, Abd (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
The main point of this research is Urf's view of the Mabbollo tradition in Bugis marriage customs in Bone Regency. The main problem consists of two sub-problems, namely: How did the Mabbollo Tradition come about in Bone Regency? And what is the urf analysis of the Mabbollo Tradition in Bone Regency? The results of this research show that Mabbollo in Bugis marriage customs in Bone Regency, is 1). For those who are pro, they really believe that if an unmarried older sister should be stepped into marriage by her younger sister, they believe that the older sister's life in the future will not go smoothly. good, especially for marriage issues. Meanwhile, those who are against it do not agree with this custom because according to them it will only have bad effects, especially for the younger sibling's mental health. 2). Mabbolla, viewed from the results of the Urf Analysis, is not prohibited, but rather recommends marriage as long as a person is capable, both physically and spiritually, as long as the marriage has been fulfilled in harmony and conditions. The Mabbollo tradition can give mashlah to special families, it can strengthen the ties of friendship between older brothers and sisters. who overstepped his marriage.